Pengembangan Metode Pengukuran Usabilitas Surel Dengan Fuzzy AHP Menurut Dimensi ISO 9421 Part 11 - Yustin Astri Andalia; Irwan Iftadi; Wachid Ahmad Jauhari (Performa: Media Ilmiah Teknik Industri, 2014)
Since 1980, there were many free emails launched. Slowly, people only choose some email providers. For known email providers have differences the number of user. For known email providers have differences the number of user. In recent years, user seems to use free email. It indicates that there are the most favourite email were choosed by user. This is because the email have more usable than others. The aim of this research is to propose usability characteristic of email and to get value from usability of email. This research methodology consist of five steps, such as: to clasify the atributtes to usability dimension, to determine criteria for usability atributes, to give value to use Fuzzy AHP, to normalize scale with OMAX, and to try measurement tool. This research result usability tools that have 3 dimensions, 24 attributes, and 11 criterias of email usability. Beside, it shows that effectivity dimension is the important dimension with wight 0,3996. Based on the resulting on try measurement tool kwon that the best email usability is Gmail with value 2,83.